2014
DOI: 10.9734/ijpss/2014/6489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pigeon Pea-Groundnut Intercropping System on Selected Soil Properties

Abstract: On average Malawi is losing of 40 kg N ha -1 and 6.6 kg P ha -1 annually. Additionally, nutrient use efficiency (NUE) is low as a result of declining levels of soil organic matter (SOM) and associated deficiencies of other macro and micronutrients. This is usually below 20 kg maize grain kg -1 of nutrients applied. To investigate on the possibility of improving NUE a study was initiated in the 2011/12 cropping season with a parallel trial mounted along side in the second season, both were laid in a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These coarse textures control the variability of nutrient storage capacity, limit the water holding capacity and roots may grow under sub-optimal soil water due to water deficits [24]. The textural classes observed coupled with the low CEC (<12 cmol (+)/kg) suggest potential leacheability of nutrient elements especially nitrogen as nitrate [25,26]. The sand content decreased gradually with depth as the proportion of finer particles increased, partially due to illuviation and argillation in the Bt horizons [27].…”
Section: Soil Morphological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These coarse textures control the variability of nutrient storage capacity, limit the water holding capacity and roots may grow under sub-optimal soil water due to water deficits [24]. The textural classes observed coupled with the low CEC (<12 cmol (+)/kg) suggest potential leacheability of nutrient elements especially nitrogen as nitrate [25,26]. The sand content decreased gradually with depth as the proportion of finer particles increased, partially due to illuviation and argillation in the Bt horizons [27].…”
Section: Soil Morphological Propertiesmentioning
confidence: 99%
“…The NH 4 + originated from the surface applied nitrogenous fertilizers (DAP 18:46:0) as a soil fertility strategy by the farmers over the four cropping seasons [43]. The low soil pH values suggest possible low availability of both macro and micro nutrients for uptake by crops [26,28]. The basic cations (K, Na) decreased while Ca and Mg increased and can be attributed to the pH.…”
Section: Soil Fertility Evaluation/trends Based On the Composite Sampmentioning
confidence: 99%
“…) and pigeon pea-soybean (53.6 kg N ha -1 ) whereas Phiri et al (2014) reported soil fertility improvement due to pigeon pea-groundnut intercrop. However, not much has been done to evaluate quantities of biologically fixed N under doubled-ups involving most of the recent legume varieties and information on pigeon pea-cowpea doubledup BNF is scanty.…”
Section: Introductionmentioning
confidence: 99%